InfoSphere: navigating the world of information ; preserving the past, valuing present, enriching the future - Md Ajis, Ahmad Fuzi; A.Jamil@Kamarudzzaman,, Azura; Mat Kamal, Siti Nuur-Ila; Abd Rahman, Nor Diana; Ahmad, Rohayu; Kamarudin, Nurfaizah; Baharin, Siti Hajar; Dahari, Siti Nur Shahira; Mohamed, Nor Rashidah; Mustapa, Maziah; Rabiatul Adawiyah, Kamarulzaman; Jamil, Nurul Huda Izzati; et al. (Universiti Teknologi MARA Cawangan Johor, 2025)
InfoSphere: Navigating the World of Information, a collective effort that brings together insightful discussions, empirical findings, and critical reflections from academics in information management, library management, records management, and information and communication technology (ICT). In today’s digital era, the vast and complex landscape of information continues to expand at an unprecedented pace. The convergence of technology and information systems has transformed how data is created, organised, stored, and utilised. This book aims to navigate that dynamic “infosphere”, a term that reflects the interconnected environment in which information flows seamlessly across platforms, disciplines, and contexts. The chapters compiled here explore diverse perspectives and contemporary issues shaping the management of information resources and services. From emerging trends in digital librarianship and knowledge governance to innovations in ICT applications and record-keeping practices, each contribution highlights the growing importance of integrating technology, policy, and human expertise in managing information effectively. This publication also serves as a reflection of our faculty’s commitment to advancing scholarship and practice in the information domain. It showcases the intellectual depth and interdisciplinary collaboration among academics who continue to shape the future of information work.